Análisis iconológico de la representación de la muerte en la fábula fantástica mexicana Macario (1960) de Roberto Gavaldón - Reyes Avilés, Saray (Eikón / Imago, 2024)
This research work is focused on the iconological analysis of the allegory of death, identifying the Mexican elements of popular tradition, which appear in said representation, with the aim of specifying the ideological contents that are conveyed in the film Macario (1960) by Roberto Gavaldon. This study is carried out based on Erwin Panofsky’s iconographic methodology, which emphasizes the link between visual elements a specific time and context. From the beginning of the film narration we can notice that, in Macario, death is subverted giving a different meaning to the one that this character originally had in The Godson of Death (1815) by the Grimm brothers and from the text by B. Traven; Emilio Carballido and Roberto Gavaldón manipulate an ideology, where death is humanized, losing its character as an inescapable fact. Another dissonance between the versions of the original story is that death is represented as a woman, while in Macario it is personified as a man and he does not sponsor him, he makes him a compadre, treats him with friendship and closeness, as suggested by the godfather; giving it a friendly, democratic character and without distinction treatment of equals.